2013
DOI: 10.1002/syn.21672
|View full text |Cite
|
Sign up to set email alerts
|

GET73 increases rat extracellular hippocampal CA1 GABA levels through a possible involvement of local mGlu5 receptor

Abstract: N-[(4-trifluoromethyl) benzyl] 4-methoxybutyramide (GET73) is a newly synthesized compound displaying anti-alcohol and anxiolytic properties. In light of the importance of the hippocampal CA1 subregion in alcohol addiction and anxiety-like behaviors-this in vivo microdialysis study characterized the effect of GET73 on extracellular GABA levels in the hippocampal CA1 region of the freely moving rat-including a possible role for mGlu5 receptor in mediating this effect. Both intraperitoneal administration (2-10 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 47 publications
(59 reference statements)
1
14
0
Order By: Relevance
“…GET 73 seems to partially act like a mGluR5 antagonist or negative allosteric modulator (Beggiato et al, 2013; Ferraro et al, 2011). GET 73 has been proposed as a potential novel pharmacotherapy for AUD and/or obesity.…”
Section: Introductionmentioning
confidence: 99%
“…GET 73 seems to partially act like a mGluR5 antagonist or negative allosteric modulator (Beggiato et al, 2013; Ferraro et al, 2011). GET 73 has been proposed as a potential novel pharmacotherapy for AUD and/or obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, low nanomolar GET73 concentrations seemed to exert a negative modulation at mGluR5, and a possible amplification of MPEP-induced effects. On the other hand, the effects of higher (i.e., μM) GET73 concentrations were counteracted by MPEP, suggesting that the compound might also exert a positive modulation at mGluR5 ( Ferraro et al, 2011 , 2013 ; Beggiato et al, 2013 ). Relevantly, the postulated ability of GET73 to negatively modulate mGluR5 may likewise explain, at least partially, its efficacy in reducing rat alcohol intake, as shown for several other compounds acting as NAM at mGluR5 ( Olive, 2009 ; Duncan and Lawrence, 2012 ; Ferraro et al, 2013 ; Holmes et al, 2013 ; Mihov and Hasler, 2016 ; Goodwani et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, low nM concentrations exerted a negative modulation at mGluR5, and a possible amplification of MPEP-induced effects. On the other hand, the GET73-induced increase in glutamate and GABA signaling, exerted at higher μM concentrations, were counteracted by MPEP, suggesting that GET73 might also exert a positive modulation at mGluR5, at least in the model employed for those studies ( Ferraro et al, 2011 , 2013 ; Beggiato et al, 2013 ). However, the above studies only indirectly suggested the existence of a possible interaction between GET73 and mGluR5.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations